Transmission Line Fault Detection and Classification for Overhead Cables Using MATLAB Software - N.Kannadhas, Jashveendas; Ismail, Muhammad Nafis (Evolution in Electrical and Electronic Engineering, 2024)
The prompt and exact detection of problems in transmission line systems is vital for assuring dependable operation and sustaining service continuity. This study intends to replicate the detection and categorization of faults in a 33kV transmission line system. Faults in transmission lines occur when two or more conductors has contact with each other or the ground, resulting to poor power quality and potential damage to electrical equipment. In this research, MATLAB Simulink software is employed to construct a model of a transmission line and to simulate several sorts of faults, including single line-to-ground faults, line-to-line faults, double line-to-ground faults, and triple line-to-ground faults. A wavelet transform-based technique is then utilized for fault identification and classification inside the modeled three-phase system. This approach employs the energy percentage at the greatest degree of approximation and the maximum threshold value, adopting a "remove near-zero" strategy by compressing the signal to identify distinct fault circumstances. The results reveal that this technique can successfully distinguish and categorize fault situations, boosting the reliability of fault detection in power transmission systems.